Systems analysis of subjects acutely infected with the Chikungunya virus - Soares-Schanoski, Alessandra; Baptista Cruz, Natália; de Castro-Jorge, Luíza Antunes; de Carvalho, Renan Villanova Homem; Santos, Cliomar Alves dos; Rós, Nancy da; Oliveira, Úrsula; Costa, Danuza Duarte; Santos, Cecília Luíza Simões dos; Cunha, Marielton dos Passos; Oliveira, Maria Leonor Sarno; Alves, Juliana Cardoso; et al. (PLoS pathogens, 2019)
The largest ever recorded epidemic of the Chikungunya virus (CHIKV) broke out in 2004 and affected four continents. Acute symptomatic infections are typically associated with the onset of fever and often debilitating polyarthralgia/polyarthritis. In this study, a systems biology approach was adopted to analyze the blood transcriptomes of adults acutely infected with the CHIKV. Gene signatures that were associated with viral RNA levels and the onset of symptoms were identified. Among these genes, the putative role of the Eukaryotic Initiation Factor (eIF) family genes and apolipoprotein B mRNA editing catalytic polypeptide-like (APOBEC3A) in the CHIKV replication process were displayed. We further compared these signatures with signatures induced by the Dengue virus infection and rheumatoid arthritis. Finally, we demonstrated that the CHIKV in vitro infection of murine bone marrow-derived macrophages induced IL-1 beta production in a mechanism that is significantly dependent on the inflammasome NLRP3 activation. The observations provided valuable insights into virus-host interactions during the acute phase and can be instrumental in the investigation of new and effective therapeutic interventions.